“ADAPTING TO A CHANGING WORLD: STRATEGIES FOR MITIGATING THE GLOBAL CONSEQUENCES OF CLIMATE CHANGE” - FRANK FUNKEYE SAPELE; AKUMKA JOSEPH YABAYANZE; KANYINSOLA AZEEZ (International Studies Journal)
This research focuses on global climate change and adaptation strategies. Climate change globally has become one of the shocking certainties of the 21st era and it has made scientists to raise the need to drop worldwide temperatures further by 0.5 °C which makes a substantial difference in some areas of the world, particularly developing countries that are faced with the greater threat of climate change.  Developing States have become exposed to the damaging effects of climate change because of their varied climatic regions and these have affected their food production activities due to the deforestation problem, desertification, soil degradation, erosion, flooding, general habitat loss, depletion of natural resources etc. This study therefore attempts to examine the extent to which continuous climate change has affected the globe and how institutional frameworks have addressed the current situation in ensuring effective control across the globe. The research employed purely on secondary means to gathered data. This research structures its opinions with the human security model as its theoretical framework. Major findings showed that environmental degradation, desertification caused by climate change had greatly stunted agricultural production and government rules universally; climate change has increased food uncertainty, poor statistical analysis and implementation by government. The paper recommends that government should provide alternative means   like renewable energy, reduction of industrial carbons in tackling the menace of climate change globally, there should be reduction of emission of greenhouse gases by stopping deforestation, the use of high yield and disease tolerant crops, and also crops adaptable to high level of weather conditions, there should be easy accessible information on climate change effects to the public.